[products of binomials][section 37]

(1.)  (y - 5)(y + 1)           here is the problem

=    y2 + y - 5y - 5      foil multiply

=   y2 - 4y - 5          combine like terms

result:  y2 - 4y - 5

(2.)  (p + 9)(p + 11)         here is the problem

=    p2 + 11p + 9p + 99       foil multiply

=   p2 + 20p + 99            combine like terms

result:  p2 + 20p + 99

(3.)  (m + n)(m - n)           here is the problem

=    m2 - mn + mn - n2       foil multiply

=    m2 - n2                combine like terms

result:  m2 - n2

(4.)  (m - n)(p - q)          here is the problem

=   mp - mq - np - nq        foil multiply

result:  mp - mq - np - nq

(5.)  (3x - 2y)(3x + 2y)        here is the problem

=    9x2 + 6xy - 6xy - 4y2      foil multiply

=    9x2 - 4y2            combine like terms

result: 9x2 - 4y2

(6.)  (m + 7)(m - 11)         here is the problem

=    m2 - 11m + 7m - 77      foil multiply

=    m2 - 4m - 77           combine like terms

result: m2 - 4m - 77

(7.)  (y2 + 3)(y2 + 3)        here is the problem

=    y4 + 3y2 + 3y2 + 9     foil multiply

=   y4 + 6y2 + 9           combine like terms

result:  y4 + 6y2 + 9

(8.)  (5x + 3)(x + 1)          here is the problem

=    5x2 + 5x + 3x + 3           foil multiply

=    5x2 + 8x + 3              combine like terms

result:  5x2 + 8x + 3

(9.)  (10p + 3)(6p - 1)         here is the problem

=    60p2 - 10p + 18p - 3       foil multiply

=   60p2 + 8p - 3              combine like terms

result: 60p2 + 8p - 3

(10.)  (2x + 5)(3x + 1)            here is the problem

=     6x2 + 2x + 15x + 5          foil multiply

=      6x2 + 17x + 5              combine like terms

result: 6x2 + 17x + 5